Pertanggungjawaban Pidana Pengguna Anggaran Makan Dan Minum (Studi Putusan MA RI No 832 K/Pid.Sus/2017) - Annisyah Sahaya Ahmad; Elsa Rina Maya Toule; Jacob Hattu (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT : This study discusses the legal arrangements regarding the procurement of goods and services in relation to criminal acts of corruption and the criminal responsibility of perpetrators of corruption in these cases. Purposes of the research to analyze and discuss legal arrangements regarding procurement of goods and services in relation to criminal acts of corruption and to explain criminal responsibility for perpetrators of corruption in the procurement of food and drink budgets for Members of the DPRD Kota Tual for the 2010 Fiscal Year in terms of the PTPK Law. The research method used is normative juridical research. In this study, three approaches to the problem are used, namely the statutory approach, the conceptual approach, and the case approach. Sources of data obtained are primary legal materials and secondary legal materials. The technique of collecting legal materials uses the literature study method. All data in this study were analyzed qualitatively. The results of this study indicate that, legal arrangements related to the procurement of goods and services function to regulate and know procedures/procedures for good and correct implementation. The element against the law is one of the parameters in determining personal responsibility for personal mistakes committed by perpetrators. The perpetrators of corruption in this case have fulfilled the elements of the indictment charged by the Public Prosecutor and therefore the perpetrators must be held accountable for their actions. The judge's legal considerations were in accordance with the existing rules by considering aggravating circumstances as well as mitigating circumstances based on the legal facts found during the trial.